A two-stage selective hydrodesulfurization process for gasoline
Patent Information
- Application Number
- CN202510536739.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2026-10-27
AI Technical Summary
该催化剂采用氧化铝载体,P和K为助剂组分,Co和Mo为活性金属组分,尽管汽油加氢脱硫选择性有了一定程度的提高,但对烯烃饱和活性的抑制作用有限,因此,该催化剂的加氢脱硫选择性还有待于进一步提高
1、烯烃加氢饱和是放热反应,对不饱和烃含量较高的油品加氢,对催化剂床层温升的控制至关重要。本发明的两段汽油选择性加氢脱硫方法,可适度地控制催化剂床层的温升。将低金属含量的催化剂装在反应器上部,使得进入反应器的原料首先接触活性相对较低的催化剂,以减缓剧烈的放热反应,让反应缓和地进行,可提高FCC汽油HDS选择性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of gasoline refining, and specifically relates to a two-stage selective hydrodesulfurization method for gasoline. Background Technology
[0002] SO2, a combustion product of sulfur compounds in gasoline X It is one of the main harmful substances in automobile exhaust. Governments around the world are working hard to reduce the emission of harmful substances in internal combustion engine exhaust. FCC gasoline has a high content of sulfur and olefins. Although the traditional HDS method can effectively remove sulfur-containing compounds, olefins are very easy to hydrogenate and saturate to form alkanes with low octane numbers, which is inevitably accompanied by a sharp drop in octane number.
[0003] CN111111701A discloses a hydrodesulfurization catalyst and its preparation method. The preparation method of the hydrodesulfurization catalyst includes the following steps: (1) loading active metals Co and Mo onto a support, drying and calcining to obtain a semi-finished catalyst; (2) saturating the semi-finished catalyst with liquid olefins, and then heat-treating it; (3) subjecting the heat-treated catalyst to sulfidation treatment to obtain the catalyst. Although this catalyst, obtained through a special coking process, has longer active phase crystals and more stack layers after sulfidation, and this structure of the sulfidated catalyst has better hydrodesulfurization selectivity, the coking process inevitably damages the desulfurization activity to some extent and cannot effectively suppress the saturated active centers of olefins.
[0004] CN1488721A discloses a gasoline selective hydrodesulfurization catalyst and a two-stage selective hydrodesulfurization process. The catalyst uses an alumina support, with P and K as auxiliary components and Co and Mo as active metal components. Although the selectivity of gasoline hydrodesulfurization has been improved to some extent, its inhibitory effect on olefin saturation activity is limited. Therefore, the selectivity of this catalyst for hydrodesulfurization needs further improvement. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a two-stage selective hydrodesulfurization method for gasoline. This method combines two catalysts with good selectivity, high stability, and different activities. The method operates stably for a long time and maintains high hydrodesulfurization activity and selectivity, thus improving the economic efficiency of the equipment.
[0006] The two-stage selective hydrodesulfurization method for gasoline of the present invention includes the following: gasoline feedstock is passed sequentially through a first catalyst bed and a second catalyst bed under hydrodesulfurization process conditions to undergo hydrodesulfurization reaction and obtain desulfurization products; wherein the first catalyst bed is filled with a first hydrodesulfurization catalyst and the second catalyst bed is filled with a second hydrodesulfurization catalyst; the active metal content of the first hydrodesulfurization catalyst is lower than that of the second hydrodesulfurization catalyst; the preparation methods of the first hydrodesulfurization catalyst and the second hydrodesulfurization catalyst are as follows: active metals, alkali metals and / or alkaline earth metals are sequentially loaded onto a support and calcined under a certain concentration of CO and / or CO2 atmosphere to obtain the catalyst.
[0007] In the method of the present invention, the catalyst loading volume ratio of the first catalyst bed and the second catalyst bed is 1:4 to 4:1.
[0008] In the method of this invention, the hydrodesulfurization reaction conditions are as follows: reaction temperature is 230~320℃, preferably 250~300℃; reaction pressure is 1.0~4.0 MPa, preferably 1.6~3.2 MPa; hydrogen-to-oil volume ratio is 100~1000 Nm³. 3 / m 3 Preferred 200~800 Nm 3 / m 3 The liquid hourly space velocity (LHSV) is 1.0–10.0 h⁻¹. -1 Preferably 2.0~6.0 h -1 .
[0009] In the method of the present invention, the active metals of the first hydrodesulfurization catalyst are Mo and Co, with MoO3 accounting for 2% to 10% and CoO accounting for 0.1% to 5% based on the total weight of the catalyst.
[0010] In the method of the present invention, the active metals of the second hydrodesulfurization catalyst are Mo and Co, with MoO3 accounting for 10% to 25% and CoO accounting for 1% to 7% based on the total weight of the catalyst.
[0011] In the method of this invention, the active metal loading process is carried out by impregnation, followed by drying. The impregnation solution for the active metals Mo and Co is an aqueous solution, an acid solution, or an ammonia solution. The Mo precursor salt is generally one or more of molybdenum oxide, ammonium heptamolybdate, and ammonium tetramolybdate, and the Co precursor salt is generally one or more of basic cobalt carbonate, cobalt nitrate, and cobalt acetate. The drying conditions are: drying temperature 50~150℃, drying time 3~24 hours.
[0012] In the method of the present invention, based on the weight of the hydrodesulfurization catalyst, the content of alkali metal and / or alkaline earth metal is 1.5% to 10.0%, preferably 2.3% to 8.0%.
[0013] In the method of this invention, the loading process of the alkali metal and / or alkaline earth metal is carried out by impregnation. The impregnation solution of the alkali metal and / or alkaline earth metal is a soluble aqueous solution of the alkali metal and / or alkaline earth metal well known in the art. The alkali metal is preferably sodium and / or potassium, and the alkaline earth metal is preferably calcium and / or magnesium. The soluble alkali metal and / or alkaline earth metal salt is generally one or more of potassium nitrate, potassium chloride, potassium dihydrogen phosphate, sodium chloride, sodium carbonate, sodium bicarbonate, magnesium nitrate, calcium nitrate, magnesium chlorate, calcium chlorate, magnesium perchlorate, calcium perchlorate, magnesium acetate, calcium acetate, magnesium chloride, or calcium chloride. Drying conditions: drying temperature 50~150℃, drying time 3~24 hours.
[0014] In the method of the present invention, the CO and / or CO2 concentration of the first hydrodesulfurization catalyst is 3000 μg / g to 8000 μg / g, preferably 4000 μg / g to 6000 μg / g, and the CO and / or CO2 concentration of the second hydrodesulfurization catalyst is ≥3000 μg / g, preferably ≥6000 μg / g.
[0015] In the method of this invention, the calcination conditions for calcination treatment under CO and / or CO2 atmosphere are as follows: calcination temperature is 300~650℃, calcination time is 3~4 hours, and programmed temperature rise is adopted with a heating rate of 2~5℃ / minute.
[0016] In the method of this invention, the first and second hydrodesulfurization catalysts need to undergo sulfidation treatment before use. This sulfidation process can be performed internally or externally. The amount of sulfiding agent introduced is 90% to 150% of the theoretical sulfur requirement of the catalyst. The sulfidation process uses programmed temperature rise, maintaining a temperature of 200-350℃ for 1-16 hours. The sulfiding agent is generally one or more of carbon disulfide, dimethyl disulfide, methyl sulfide, and n-butyl sulfide.
[0017] In the method of this invention, the pore volume of the hydrodesulfurization catalyst is 0.3~1.3 mL / g, and the specific surface area is 150~400 m². 2 / g, strength 100~250N / cm, bulk density 0.65~0.90g / mL.
[0018] In the method of the present invention, the hydrodesulfurization catalyst may also include additives such as Ti, Zr, V, Cu, Zn, and Si. The additive content is 0.5% to 7% based on the total weight of the catalyst, and the sum of the contents of all components of the catalyst is 100%.
[0019] The method of the present invention has the following advantages compared with the prior art: 1. Olefin hydrogenation saturation is an exothermic reaction. For hydrogenation of oils with high unsaturated hydrocarbon content, controlling the temperature rise of the catalyst bed is crucial. The two-stage selective hydrodesulfurization (HDS) method for gasoline of this invention can moderately control the temperature rise of the catalyst bed. By placing a low-metal-content catalyst at the top of the reactor, the feedstock entering the reactor first contacts the relatively less active catalyst, thus mitigating the violent exothermic reaction and allowing the reaction to proceed more gently, thereby improving the selectivity of FCC gasoline HDS.
[0020] 2. In the preparation of hydrodesulfurization catalysts, active metals, alkali metals, and / or alkaline earth metals are first loaded, and then calcined under a certain concentration of CO and / or CO2 atmosphere. As the calcination temperature gradually increases, active metals Mo and Co can be gradually converted into oxidized states and form active centers for desulfurization and hydrogenation. Simultaneously, due to the characteristic that CO and / or CO2 easily adsorb onto the active sites of the hydrodesulfurization reaction, CO and / or CO2 better protect the active sites of the hydrodesulfurization reaction during the gradual conversion of active metals Mo and Co into oxidized states to form active centers. At the same time, alkali metals and / or alkaline earth metals are also synchronously and gradually converted into oxidized states. Alkali metals and / or alkaline earth metals are catalyst poisons and can inhibit catalyst activity. This inhibitory effect, under the protection of the active sites of the hydrodesulfurization reaction by CO and / or CO2 molecules, is more likely to act on the active sites of olefin hydrogenation saturation reaction during the gradual conversion of active centers, further inhibiting olefin saturation activity. The entire process is completed during the gradual formation of the active phase, enhancing the hydrodesulfurization activity and selectivity of the catalyst, achieving the purpose of selective hydrodesulfurization of gasoline. The low- and high-metal catalysts were prepared under different concentrations of CO and / or CO2 atmospheres to achieve optimal catalyst preparation results. This invention uses a two-stage impregnation process with only one calcination step to obtain the finished catalyst, simplifying the process and reducing energy consumption. Detailed Implementation
[0021] In this invention, the specific surface area and pore volume were determined using a cryogenic liquid nitrogen adsorption method. In this invention, % represents mass percentage. The catalyst composition was determined using a titration method.
[0022] The specific preparation process of the hydrodesulfurization catalyst of the present invention is as follows: the support is impregnated with an impregnation solution containing active metals Mo and Co, dried at 50~150℃ for 3~24 hours, then impregnated with an impregnation solution containing alkali metals and / or alkaline earth metals, dried at 50~150℃ for 3~24 hours, and calcined at 300~650℃ for 3~4 hours under an atmosphere of ≥3000μg / g CO and / or CO2 at a programmed heating rate of 2~5℃ / min to obtain the hydrodesulfurization catalyst.
[0023] In the above preparation method, the concentration of the impregnation solution is determined by the water absorption rate and the required catalyst composition (content).
[0024] The selective hydrodesulfurization process for gasoline according to the present invention is as follows: Under hydrodesulfurization conditions, the feedstock and hydrogen are sequentially reacted with a first hydrodesulfurization catalyst and a second hydrodesulfurization catalyst. The loading ratio of the first hydrodesulfurization catalyst and the second hydrodesulfurization catalyst in the reactor is 2 / 8 to 8 / 2, preferably 3 / 7 to 8 / 2, and most preferably 4 / 6 to 8 / 2. The following examples specifically illustrate the two-stage selective hydrodesulfurization process using the catalyst of the present invention and the catalyst used. Example 1
[0025] 200g of alumina support was impregnated with 190 mL of a molybdenum and cobalt ammonia solution containing 11.2g of cobalt carbonate and 22.5g of ammonium molybdate, and dried at 110℃ for 5 hours to obtain the first material. The first material was then impregnated with 120 mL of an aqueous solution containing 16.6g of potassium dihydrogen phosphate, and dried at 110℃ for 5 hours to obtain the second material. Under a CO2 atmosphere of 5900μg / g, the second material was calcined at 550℃ for 3 hours at a programmed heating rate of 3℃ / min to obtain the finished catalyst A. Example 2
[0026] 200g of alumina support was impregnated with 190 mL of a molybdenum and cobalt ammonia solution containing 5.2g of cobalt carbonate and 11.4g of ammonium molybdate, and dried at 110℃ for 5 hours to obtain the first material. The first material was then impregnated with 130 mL of an aqueous solution containing 16.6g of potassium dihydrogen phosphate, and dried at 110℃ for 5 hours to obtain the second material. The second material was then calcined at 500℃ for 3 hours under a CO atmosphere with a programmed heating rate of 3℃ / min to obtain the finished catalyst B. Example 3
[0027] 200g of alumina support was impregnated with 190 mL of a molybdenum and cobalt ammonia solution containing 14.3g of cobalt carbonate and 36.3g of ammonium molybdate, and dried at 110℃ for 5 hours to obtain the first material. The first material was then impregnated with 110 mL of an aqueous solution containing 17.6g of potassium dihydrogen phosphate, and dried at 110℃ for 5 hours to obtain the second material. The second material was then calcined at 500℃ for 3 hours at a programmed heating rate of 3℃ / min under an atmosphere of 3000μg / g CO and 3800μg / g CO2 to obtain the finished catalyst C. Example 4
[0028] 200g of alumina support was impregnated with 190 mL of a molybdenum and cobalt ammonia solution containing 19.8g of cobalt carbonate and 47.3g of ammonium molybdate, and dried at 110℃ for 5 hours to obtain the first material. The first material was then impregnated with 110 mL of an aqueous solution containing 13.7g of potassium nitrate, and dried at 110℃ for 5 hours to obtain the second material. The second material was then calcined at 500℃ for 3 hours under a CO2 atmosphere with a heating rate of 3℃ / min to obtain the finished catalyst D.
[0029] Comparative Example 1 Same as Example 1, except that instead of CO2 atmosphere, air atmosphere was used to obtain the finished catalyst E.
[0030] Comparative Example 2 Same as Example 2, except that 200g of alumina support was impregnated with 190 mL of a molybdenum and cobalt ammonia solution containing 5.2g of cobalt carbonate and 11.4g of ammonium molybdate, dried at 110°C for 5 hours, and then calcined at 500°C for 3 hours at a programmed heating rate of 3°C / min to obtain hydrodesulfurization catalyst F.
[0031] Comparative Example 3 Same as Example 3, except that the first material is not impregnated with 110 mL of an aqueous solution containing 17.6 g of potassium dihydrogen phosphate to obtain the finished catalyst G.
[0032] Comparative Example 4 Same as Example 4, except that the CO2 content was always kept at 700 μg / g under the same atmospheric conditions to obtain the finished catalyst H. Example 5
[0033] In a 200 mL fixed-bed small-scale hydrogenation unit, catalyst A and catalyst B were used in the first stage, and catalyst C and catalyst D were used in the second stage. The catalyst loading ratios for the first and second stages were 5 / 5 and 3 / 7, respectively. The reaction pressure was 1.6 MPa and the liquid hourly space velocity was 3.0 h⁻¹. -1 The hydrogen-to-oil volume ratio is 300 Nm 3 / m 3 Selective hydrodesulfurization was carried out on raw materials with a sulfur content of 664 μg / g and RON of 93.0 at a reaction temperature of 270℃.
[0034] Comparative Example 5 The evaluation method is the same as in Example 7, with catalyst E used in the first stage and catalyst G used in the second stage. The loading ratio of the catalysts in the first and second stages is 5 / 5.
[0035] Comparative Example 6 The evaluation method is the same as in Example 5, with catalyst F used in the first stage and catalyst H used in the second stage. The loading ratio of the catalysts in the first and second stages is 3 / 7. Example 6
[0036] This example compares the physicochemical properties of the catalysts prepared in the above examples with the results of operating the above examples on a small-scale hydrogenation unit for 600 hours, as shown in Tables 1 and 2.
[0037] Table 1. Main properties of the catalyst Catalyst number A B C D E F G H <![CDATA[MoO3,wt%]]> 8.1 4.2 11.9 15.8 8.1 4.2 11.9 15.8 CoO, wt% 2.5 1.4 3.2 4.0 2.5 1.4 3.2 4.0 <![CDATA[K2O,wt%]]> 2.6 2.7 2.5 2.7 2.6 2.7 - 2.7 Pore volume, mL / g 0.43 0.48 0.47 0.42 0.41 0.46 0.49 0.43 <![CDATA[Specific surface area, m 2 / g]]> 245 249 224 208 235 241 243 226 Table 2 Catalyst Activity and Selectivity
[0038] Reaction conditions: P = 1.6 MPa; LHSV = 3.0 h⁻¹ -1 H2 / Oil = 300 Nm 3 / m 3 Table 2 shows that the two-stage selective hydrodesulfurization process of this invention results in less octane number loss under the same desulfurization rate. After a certain operating time, the catalyst of this invention exhibits good activity and selectivity, and its selective hydrodesulfurization performance is more stable than that of the comparative catalyst.
[0039] Reaction conditions: P = 1.6 MPa; LHSV = 3.0 h⁻¹ -1 H2 / Oil = 300 Nm 3 / m 3 Table 2 shows that the two-stage selective hydrodesulfurization process of this invention results in less octane number loss under the same desulfurization rate. After a certain operating time, the catalyst of this invention exhibits good activity and selectivity, and its selective hydrodesulfurization performance is more stable than that of the comparative catalyst.
Claims
1. A two-stage selective hydrodesulfurization method for gasoline, characterized in that... The process includes the following: gasoline feedstock undergoes hydrodesulfurization under hydrodesulfurization conditions, passing sequentially through a first catalyst bed and a second catalyst bed to produce desulfurization products; wherein the first catalyst bed is filled with a first hydrodesulfurization catalyst, and the second catalyst bed is filled with a second hydrodesulfurization catalyst; the active metal content of the first hydrodesulfurization catalyst is lower than that of the second hydrodesulfurization catalyst; the preparation methods of the first hydrodesulfurization catalyst and the second hydrodesulfurization catalyst are as follows: active metals, alkali metals, and / or alkaline earth metals are sequentially loaded onto a support, and calcined under a certain concentration of CO and / or CO2 atmosphere to obtain the catalyst.
2. The method according to claim 1, characterized in that: The catalyst loading volume ratio of the first catalyst bed and the second catalyst bed is 1:4 to 4:
1.
3. The method according to claim 1, characterized in that: The hydrodesulfurization reaction conditions are as follows: reaction temperature is 230~320℃, preferably 250~300℃; reaction pressure is 1.0~4.0 MPa, preferably 1.6~3.2 MPa; hydrogen-to-oil volume ratio is 100~1000 Nm³. 3 / m 3 Preferred 200~800 Nm 3 / m 3 The liquid hourly space velocity (LHSV) is 1.0–10.0 h⁻¹. -1 Preferably 2.0~6.0 h -1 .
4. The method according to claim 1, characterized in that: The active metals of the first hydrodesulfurization catalyst are Mo and Co, with MoO3 accounting for 2% to 10% and CoO accounting for 0.1% to 5% based on the total weight of the catalyst.
5. The method according to claim 1, characterized in that: The active metals of the second hydrodesulfurization catalyst are Mo and Co, with MoO3 accounting for 10% to 25% and CoO accounting for 1% to 7% based on the total weight of the catalyst.
6. The method according to claim 1, characterized in that: The active metal loading process is carried out by impregnation, followed by drying. The impregnation solution for the active metals Mo and Co is an aqueous solution, an acid solution, or an ammonia solution. The precursor salt of Mo is one or more of molybdenum oxide, ammonium heptamolybdate, and ammonium tetramolybdate. The precursor salt of Co is one or more of basic cobalt carbonate, cobalt nitrate, and cobalt acetate. The drying conditions are: drying temperature 50~150℃, drying time 3~24 hours.
7. The method according to claim 1, characterized in that: Based on the weight of the hydrodesulfurization catalyst, the content of alkali metals and / or alkaline earth metals is 1.5% to 10.0%, preferably 2.3% to 8.0%.
8. The method according to claim 1, characterized in that: The loading process of the alkali metal and / or alkaline earth metal adopts an impregnation method. The impregnation solution of the alkali metal and / or alkaline earth metal is a soluble aqueous solution of the alkali metal and / or alkaline earth metal. The alkali metal is preferably sodium and / or potassium, and the alkaline earth metal is preferably calcium and / or magnesium. Drying conditions: drying temperature 50~150℃, drying time 3~24 hours.
9. The method according to claim 1, characterized in that: The first hydrodesulfurization catalyst uses a CO and / or CO2 concentration of 3000 μg / g to 8000 μg / g, preferably 4000 μg / g to 6000 μg / g; the second hydrodesulfurization catalyst uses a CO and / or CO2 concentration of ≥3000 μg / g, preferably ≥6000 μg / g.
10. The method according to claim 1, characterized in that: The roasting conditions for roasting under CO and / or CO2 atmosphere are: roasting temperature of 300~650℃ and roasting time of 3~4 hours.
11. The method according to claim 1, characterized in that: Before use, the first and second hydrodesulfurization catalysts need to undergo sulfidation treatment, which can be carried out through an in-unit or out-of-unit sulfidation process. The amount of sulfiding agent introduced is 90% to 150% of the theoretical sulfur requirement of the catalyst. The sulfidation process adopts programmed temperature rise, and the temperature is raised to 200 to 350℃ and held at that temperature for 1 to 16 hours. The sulfiding agent is generally one or more of carbon disulfide, dimethyl disulfide, methyl sulfide, and n-butyl sulfide.
12. The method according to claim 1, characterized in that: The first and second hydrodesulfurization catalysts have the following properties: pore volume of 0.3~1.3 mL / g and specific surface area of 150~400 m². 2 / g, strength 100~250N / cm, bulk density 0.65~0.90g / mL.
13. The method according to claim 1, characterized in that: The first and second hydrodesulfurization catalysts also include Ti, Zr, V, Cu, Zn, and Si additives. The additive content is 0.5% to 7% by weight of the total catalyst, and the sum of the contents of all catalyst components is 100%.
Citation Information
Patent Citations
Hydrodesulfurization catalyst and preparation method thereof
CN111111701A